2023
DOI: 10.3390/jcm12020637
|View full text |Cite
|
Sign up to set email alerts
|

Association between Serum Soluble α-Klotho and Urinary Albumin Excretion in Middle-Aged and Older US Adults: NHANES 2007–2016

Abstract: (1) Background: Preclinical and clinical studies on the anti-aging effect of α-Klotho are emerging. Urinary albumin excretion (UAE) is a well-known biomarker of kidney injury and generalized damage in the cardiovascular system. However, the potential relationship between α-Klotho and UAE is limited and controversial. This study aimed to quantify this relationship in the general middle-aged and elderly population from the National Health and Nutrition Survey (NHANES) 2007–2016. (2) Methods: Serum α-Klotho was m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 70 publications
1
8
0
Order By: Relevance
“…The associations between low serum and urinary Klotho and albuminuria in patients with T2D were noted in previous studies [ 48 , 59 , 60 ]. Some experimental data may help explain the mechanism of this relationship.…”
Section: Discussionsupporting
confidence: 68%
“…The associations between low serum and urinary Klotho and albuminuria in patients with T2D were noted in previous studies [ 48 , 59 , 60 ]. Some experimental data may help explain the mechanism of this relationship.…”
Section: Discussionsupporting
confidence: 68%
“…Interestingly, when we analyzed the relationship between Klotho concentration and inflammatory biomarkers, lipid biomarkers and renal function biomarkers, we found that Klotho had a threshold effect in the same concentration range, suggesting that there was an optimal concentration range (around 1000 pg/ml) for Klotho to exert its biological function. A recent study found that all-cause mortality was lowest in the general population at Klotho concentrations around 1000 pg/ml (961.4 to 1140.0 pg/ml) [82]. These findings provided a basis for clinically monitoring Klotho concentration, but the precise concentration range required further investigation.…”
Section: Klotho Could Reduce the Risk Of All-cause Mortality In Gener...mentioning
confidence: 99%
“…Urinary albumin and creatinine levels were measured from a single spot urine sample utilizing solid-phase fluorescence immunoassay and a modified Jaffe kinetic method ( 12 ). The UACR was computed by dividing the concentration of urinary albumin (mg) by the concentration of urinary creatinine (g).…”
Section: Methodsmentioning
confidence: 99%
“…This phenomenon is frequently regarded as the most sensitive and dependable diagnostic marker for the early identification of chronic kidney disease (CKD) in cases where the estimated glomerular filtration rate (eGFR) is within the normal range. Furthermore, it is linked to unfavorable health outcomes ( 11 , 12 ). In addition, UAE has also been shown to be an independent predictor of CKD progression and cardiovascular risk ( 7 , 13 ).…”
Section: Introductionmentioning
confidence: 99%